Upaya Peningkatan Keterampilan Berbicara Menggunakan Bahasa Inggris Siswa-Siswi SMA Kristen Kalam Kudus Sukoharjo dengan Melibatkan Mahasiswa sebagai Speaking Buddies - Hadiyanto, Anita Kurniawati; Setiamunadi, Antonina Anggraini; Kisnanto, Yustina Priska (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Speaking as one of the productive skills is very important to be mastered by English language learners. However, teaching English in the context of English as a Foreign Language (EFL) has several challenges. Besides limited exposure to the language, another biggest challenge is that there are very few opportunities available for students to practice speaking in English. For this reason, SMA Kristen Kalam Kudus Sukoharjo held an extracurricular activity which is called as English Conversation Club (ECC) activity in collaboration with the English Language Education Program of Universitas Kristen Satya Wacana Salatiga by involving eight of the lecturers as instructors and nine students. This activity which aims to improve students' English skills used peer tutoring as its method. This activity was carried out as many as 8 online meetings through Zoom. The results of observations done by the instructors on the role of speaking buddies during the 8 meetings showed that the problems that were often faced by students when practicing speaking in English could be solved through the involvement of speaking buddies. In this activity, the speaking buddies play several roles in various activity sessions, such as organizers, resources, language controllers, and prompters.